Changing Contexts, New Texts: ‘‘Inserting’’ TV into the Transforming Text of Post-1980 Bengali Cinema - Gooptu, Sharmistha (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter analyses a profound transformation of Bengali regional-languagecinema since the early 1980s, a transformation that fundamentally changedthe industry and one that can arguably be attributed at least partly to thecreation of a Bengali television-watching public in the same period. Itfocuses on a trend that emerged in mainstream Bengali cinema during the1980s and was sustained thereafter, and brought into prominence a newconfiguration of elements previously marginal to Bengali films. This trans-formation was to do with mainstream Bengali cinema’s increasing adaptation of what are commonly known as the ‘‘masala’’ or ‘‘formula’’ elementsof Bombay cinema such as racy dialogues, stereotypical villainous char-acters, stylized fights and song-and-dance sequences. This new genre, whichhas commonly been discredited as the Bengali film industry’s totally unim-aginative imitation of the popular Hindi-language cinema of Bombay,completely altered what had been the dominant aesthetic of Bengali cinematill about the mid-1970s. Until this point, Bengali cinema was marked by itsclose relationship with Bengali literature and a Bengali middle-class worldview, greater realism than Bombay cinema or other mainstream regionalcinemas, and naturalistic acting styles, and was radically transformed by agrowing adoption of the ‘‘formula’’ elements commonly identified withpopular Hindi cinema. Industry sources, however, indicate that this newtrend was successful in boosting the Bengali film industry, which had beenswamped by a severe economic crisis since the 1970s. The industry’s crisiswas caused by a host of factors: the most important of these was the Ben-gali middle-class audience’s shift to television as a result of an increasingly unsatisfactory film-going experience in this period. The creation of a Ben-gali television public in the early 1980s shifted audiences from the cinematheatres, thereby significantly reducing film revenues in Calcutta, until then the prime market for Bengali films.
Keywords: 1-Cinéma; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Cultural Polysemy and Vernacular Cosmopolitanism in the Theme Songs of Hong Kong Television Dramas - Kai Khiun, Liew (Television Histories in Asia, 2015)
In 1980, Hong Kong’s commercial Television Broadcast Limited (TVB) television drama The Bund ( 上海滩 ) was popularly received in the city as well as in South-East Asia and the broader Chinese diaspora. Set in the cosmopolitan treaty port of Shanghai in the 1920s, The Bund revolves around the violent ascent of a coolie (Ray Lui) and a disillusioned student activist (Chow Yun-Fat) to become prominent mobsters. Not only were two sequels made within that year, but this historical gangster drama has been repeatedly resurrected in television dramas and fi lms, including Chow’s redux, The Last Tycoon ( 大上海 ), three decades later in 2012. From karaoke lounges to social media sites, theme songs of The Bund remain popular more than three decades after the dramas were screened . With music composed by Joseph Koo, lyrics by Wong Jim and sung by Frances Yip, the main and supplementary theme songs refl ected the intimate role of the Hong Kong-based contemporary Cantonese popular music, or Canto-pop, in cultivating a more memorable and enduring televisual culture. With the smooth synchronization of Koo’s classical music with the undulating pitch of Yip, the song articulates the unpredictable tribulations of the changing fortunes in the treaty-port of Shanghai in the interwar years. To a certain extent, it is also a narrative that reminds viewers in Hong Kong and beyond of similar socio-political and historical predicaments.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Reformatting the Format: Philippines in the Global Television Format Business - Santos, Joseﬁna M. C. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
In the eyes of many observers the Philippine cultural icon that is synonymous with travel, as well as being the subject of numerous advertisements is the jeepney, a public-transport vehicle assembled in the style of the US military jeep but lengthened to accommodate from fourteen to twenty-two sitting passengers. What distinguishes the jeepney from run-of-the-mill public transport however is its artistic décor: a clutter and kaleidoscope of various artefacts from miniature steel horses dotting the hood, to massive, jazzy plastic or steel billboards announcing the name of the jeepney, to murals painted in ﬁesta colours at the sides, to a bizarre combination of items in the front windshield juxtaposing conﬂicting images of the Sto. Nino (the baby Jesus Christ) and stickers with sexually risqué messages.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Copied from Without and Cloned from Within: India in the Global Television Format Business - Thomas, Amos Owen; Kumar, Keval J. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television programme format adaptation is becoming an increasingly signiﬁcant phenomenon in India as it is in many other countries with an active domestic television industry. Some obvious successes stand out in recent years, such as Kaun Banega Crorepati, the licensed adaptation of Celador’s global format success Who Wants To Be A Millionaire?, and C.A.T.S., a licensed Hindi version of the US detective series Charlie’s Angels. However, sensitivity to local cultural nuances has been critical to their popular reception by Indian audiences. Yet despite a few high-proﬁle licensed adaptations or copycatting, there are far more instances of unlicensed adaptations or cloning, sometimes subtle, other times not.
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); Suède (lieu de production du savoir); _Nettoyé

Coping, Cloning and Copying: Hong Kong in the Global Television Format Business - Fung, Anthony (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Hong Kong is famous internationally as a ﬁnancial market, a shopping paradise, and Chinese ﬁlm production hub, but notoriously (and perhaps even attractively for some) Hong Kong is also a hotbed of piracy of computer software, DVDs, watches and toys.1 While many cultural products such as television dramas and movies are original and quite reputable in the region, media critics argue that the copycat phenomenon, which includes borrowing, inserting and modifying other cultural texts to augment local production, is common in the media and entertainment industries (Fung 1998). Whenever a new form, style, or popular culture trend emerges in Hong Kong, market forces soon kick in to replicate it. However, this kind of reproduction, as shown by the history of cultural production in Hong Kong, does not necessarily lead to a degradation of programme quality. Reproduction is not only a savvy strategy to reduce the ﬁnancial risks inherent to new products, but also aims at producing ‘improved’ versions which can reap more proﬁts for the industry.
Keywords: 1-TV; 2-Analyses formalistes; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Cloning, Adaptation, Import and Originality: Taiwan in the Global Television Format Business - Liu, Yu-Li; Chen, Yi-Hsiang (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Taiwan residents enjoy one of the most abundant television diets in East Asia. Eighty per cent of households subscribe to cable television services, offering a buffet of more than eighty channels including niche and full service channels. Taiwan’s television industry, while relatively small in comparison with its competitors in East Asia, has established a reputation for creatively re-generating formats developed elsewhere.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

New Television, Globalisation, and the East Asian Cultural Imagination - Keane, Michael; Fung, Anthony Y. H.; Moran, Albert (Hong Kong University Press, 2007)
This volume is divided into three parts: 'Adaptation and Local Production in East Asia', 'Formats, Clones, and Generic Variations' and 'New Television'.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Chine (corpus analysé); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); Japon (corpus analysé); Taiwan (corpus analysé); _Nettoyé

The International Encyclopedia of Media Studies: Media History and the Foundations of Media Studies - Valdivia, Angharad N.; Nerone, John C.; Mayer, Vicki; Mazzarella, Sharon R.; Parameswaran, Radhika E.; Scharrer, Erica; Darling-Wolf, Fabienne; Gates, Kelly (Wiley-Blackwell, 2013)
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé